Petrography, geochemistry and age of Cerro Frontino Gabro (2015)
The Gabro de Cerro Frontino was emplaced in the Cañasgordas Block, located in the Northern Segment of the Colombian Western Cordillera. It corresponds to a pluton composed of at least three magmatic pulses, emplaced during a short period of time. Gabbros and diorites are more common in the unit than clinopiroxenites, monzodiorites and monzonites. These rocks are composed of calcic to intermediate plagioclase, augite-egerine type clinopyroxene and biotite; olivine and flogopite may be present in some mafic rocks and alkali feldspar and quartz may be present in some felsic rocks. Sphene, magnetite and apatite are common accessory minerals. The silica content in the rocks varies between 37.08% and 54.4%, with constant values of MnO (0.1% 0.4%), impoverishment of Fe2O3, MgO, CaO, TiO2 and P2O5 as SiO2 increases, and enrichment of K2O, Na2O and Al2O3 as SiO2 increases. The basic and ultrabasic rocks fall in the subalkaline series, the rest of the samples fall in the medium to K-rich calc-alkaline series and in the shoshonitic series. The Gabro de Cerro Frontino corresponds to magmas impoverished on heavy rare earth elements with respect to light rare earth elements, which suggests the contribution of a subduction component in the magma genesis. The LILE (Sr, K, Rb, Pb, Ba) are enriched with respect to the HFSE values that are relatively flat and impoverished; the unit also exhibits a negative anomaly of Nb with respect to Th and Ce, being a magmatic arc the environment of generation. The ages obtained in biotite using the Ar-Ar method fall between 9.87±0.18 Ma and 11.44±0.36 Ma, Middle to upper Miocene (Tortonian-Serravallian), similar to age of other plutons that are part of the Botón Arc.